(untitled) (International Journal of Innovative Technologies in Economy, 2022)
This article discusses the need to introduce foreign experience in the field of the information system of the treasury of the Republic of Uzbekistan. The advantages of introducing foreign experience in the context of the introduction of the digital economy are noted. Questions about the shortcomings of the current state of the information system in the treasury are considered, as well as a number of reasons hindering the development of this area. Based on the analysis of the experience of foreign countries, especially the experience of France, a number of proposals are given by the co-authors to introduce a new mechanism for the operation of the treasury information system in the Republic of Uzbekistan in the context of the introduction of the digital economy. The digital economy is changing our socio-economic development of society in an unprecedented way, while creating both huge opportunities. New technologies can make an enormous contribution to the achievement of a country’s sustainable economic development goals. However, obtaining positive results requires studying foreign experience. In order to unlock the full socio-economic potential of digital technologies, while avoiding undesirable consequences, it is necessary to strengthen international cooperation as soon as possible.